PENGENALAN EDUKASI TENTANG COVID-19 PADA ANAK USIA DINI BERBASIS VIDEO ANIMASI DAN GAMES - Nur Budi Nugraha; Ari Sellyana (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2022)
News about covid-19 has become the daily consumption of Indonesian people. The rate of transmission of the corona virus to children in Indonesia is high and requires vigilance for parents and teachers. The lack of awareness of children so that there are still many children playing in groups without paying attention to health protocols. Prevention of covid-19 transmission can be done by providing health education to them to protect children from the covid-19 virus by providing interesting information to early childhood. Providing education through animated videos and games helps capture children's memory related to information provided about preventing covid-19 and increasing body immunity during a pandemic. Interesting education makes children more interested and understand the purpose of the education. This community service activity was carried out by socializing & explaining the introduction of education about covid-19 through animated videos and games. Animated videos about covid-19 are made as attractive as possible by using animated icons and images so that children are enthusiastic in learning to understand the video. In addition, games are also inserted so that children can learn while playing so they don't get bored quickly. The result of this activity was that 90% of the children were active in asking and listening to various things about the covid-19 education that had been given. In addition, children gain new insights about covid education, besides that they can learn through animated videos while playing games so they don't feel bored quickly in participating in community service activities.